Symbolic Interactionism in Forming Self-Concept Among Individuals with Mental Disorders - Edi Nurhidin (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2026)
This research is motivated by the high prevalence of mental disorders and the persistent occurrence of discriminatory practices such as shackling in Indonesia, which actually worsen the condition of individuals with mental disorders. Furthermore, previous literature has limited exploration of the self-concept formation among individuals with mental disorders through positive symbolic interactions. Therefore, this study aims to explore alternative, more humane strategies for shaping the self-concept of Individuals with Mental Disorders (ODGJ) other than shackling. This qualitative research employed a constructivist paradigm with a case study method at the Baitul Latifa Foundation. Data were collected through participant observation and in-depth interviews using purposive sampling with seven informants, including the foundation's founder, survivors, and local residents. The study found that the foundation implemented